Education for Anthropocene Governance Part I and II - Luksha, Pavel; Laszlo, Alexander (Proceedings of the 59th Annual Meeting of the ISSS - 2015 Berlin, Germany, 2017)
As a part of our GEF forum series (see presentation & GEF future map for details), we will organize a number of vision-building participatory processes that will help create shared understanding & vision of * challenges of anthropocene: global trends that may lead us towards the desirable future (of thrivable civilization), and global trends that bring undesirable qualities (and call for creation / support of counter-trends) in next 20-30 years * skills / meta-skills that are required from different types of agents, including business, government, academia, and social movements, to support desirable qualities and mitigate risks of anthropocene in next 10-20 years * systemic innovations in education & training systems across the world that may be necessary to create such skills, that could be launched as pilots in next 2-4 years and scaled up in next 5-10 years The results of this workshop will be included in the Global Education Futures Agenda report that will conclude GEF 2015 series and will be presented in several leading international forums, including World Economic Forum. This session will also further the work of former ISSS President Bela Banathy (many of Prof. Banathy's group members have participated in our first large event in California in the beginning of April). The session also presents 'Antarctic Biennale & Foresight Fleet' project, a unique international platform for transdisciplinary dialogue on new ways of thrivable living, coupled with artistic exploration of humanity frontier themes. During the session, we will connect the project with ISSS agenda and will source contributions of ISSS experts that can be embedded in the design of Antarctic Biennale.